Precatórios no âmbito do Tribunal Regional Federal da 1ª região: efeitos da ação declaratória de inconstitucionalidade nº 4425 - FAVACHO, Iná Camila Ramos (2020)
This paper aims to examine how the effects of direct actions of unconstitutionalities n. 4425 and 4357 operate on monetary adjustment indexes and interest on arrears in the precatory system, based on judgments that took place before and after March 25, 2015, in the Federal Regional Court of the 1st Region. The present study is anchored in three chapters, with the first presenting the concepts related to the researched theme, the second expressing the argumentspresented by the Federal Supreme Court and the third covers the description of the methodology, selection of jurisprudence, analysis and interpretation of the results,in light of all the research literature, the historical context and the effects of modulation of the above mentioned ADI's.In this sense, the methodology for data collection consisted of the selection of TRF1 judgments published from September 25, 2014 to March 25, 2015 and from March 26, 2015 to September 26, 2015, verifying how the modulation of the effects of the aforementioned ADI's on the monetary correction and interest on arrears in the precatory system operates. The results indicate that there is no uniformity, in case law, in the application of monetary adjustment indices before or after modulating the effects of ADI 4425 and 4357. However, the results indicate the homogeneous application of standard by case law.